1994
DOI: 10.1121/1.410291
|View full text |Cite
|
Sign up to set email alerts
|

Automatic discrimination of phonetically relevant and irrelevant vowel parameters as reflected by mismatch negativity

Abstract: An auditory event-related brain potential called mismatch negativity (MMN) was measured to study the perception of vowel pitch and formant frequency. In the MMN paradigm, deviant vowels differed from the standards either in F0 or F2 with equal relative steps. Pure tones of corresponding frequencies were used as control stimuli. The results indicate that the changes in F0 or F2 of vowels significantly affected the MMN amplitudes. The only variable significantly affecting the MMN latencies was sex which, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 0 publications
1
21
2
Order By: Relevance
“…Because changes in MMN amplitude have been shown to predict variations in hit rates and RT (Aaltonen et al 1994;Tiitinen et al 1994;Kraus et al 1996; Amenedo and Escera Menning et al 2000), a correlation analysis between changes in MMN amplitude and changes in the RT and P r was conducted separately. A negative correlation was found between the MMN amplitude and the P r discrimination index (r = −0.83, P < 0.08), indicating that voltage values of MMN were more negative (i.e., increased amplitude) as P r increased.…”
Section: Correlation Between Behavioral and Neurophysiological Resultsmentioning
confidence: 99%
“…Because changes in MMN amplitude have been shown to predict variations in hit rates and RT (Aaltonen et al 1994;Tiitinen et al 1994;Kraus et al 1996; Amenedo and Escera Menning et al 2000), a correlation analysis between changes in MMN amplitude and changes in the RT and P r was conducted separately. A negative correlation was found between the MMN amplitude and the P r discrimination index (r = −0.83, P < 0.08), indicating that voltage values of MMN were more negative (i.e., increased amplitude) as P r increased.…”
Section: Correlation Between Behavioral and Neurophysiological Resultsmentioning
confidence: 99%
“…The MMN elicited by tones is larger over the right hemisphere (in both children and adults), irrespective of the ear stimulated [Giard et al, 1990;Korpilahti and Lang, 1994;Paavilainen et al, 1991;Csépe, 1995]. However, in response to speech stimuli, the MMN can be symmetric both in adults [Aaltonen et al, 1994;Tremblay et al, 1997] and throughout the school-age years .…”
Section: Hemispheric Symmetrymentioning
confidence: 97%
“…Although the present two MMN experiments did not include conditions with active discrimination tasks and, further, their stimulus parameters were not directly comparable, their results can be generalized to a certain extent: previously it was demonstrated that MMN reflects the perceptual accuracy in several kinds of measures such as the Seashore musicality test measuring the subjects' accuracy in sensory-level discrimination [Lang et al, 1990] and the Karma musicality test measuring the subjects' ability to structure continuous sound material to meaningful units [Tervaniemi et al, 1997;Aaltonen et al, 1994;Alho et al, 1992;Tiitinen et al, 1994;Kraus et al, 1995Kraus et al, , 1996Kraus et al, , 1998]. So, although the MMN elicitation does not require the subjects' voluntary attention it well predicts their performance under attentive control.…”
Section: Discussionmentioning
confidence: 99%
“…Its occurrence implies an incongruency between the stimulus (event) parameters coded by the cortical [Alho, 1995;Giard et al, 1990, Hari et al, 1984 neural-memory trace and new sensory information [Näätänen, 1992]. Importantly, the MMN latency and amplitude for a change in a given sound parameter correlate with the subject's and patient's accuracy in discriminating this parameter in a separate discrimination task [Aaltonen et al, 1994;Korpilahti and Lang, 1994;Kraus et al, 1995Kraus et al, , 1996Lang et al, 1990;Tervaniemi et al, 1997;Tiitinen et al, 1994]. Thus MMN provides a means for determining the severity of pathologies in auditory perception, these recordings being particularly valuable in assessing deficits in patients who are not motivated to or capable of giving their verbal or motor response during active tone discrimination [Näätänen and Alho, 1997].…”
Section: Introductionmentioning
confidence: 99%